O uso do zoológico como Instrumento pedagógico na educação ambiental (não) formal - Oliveira, Vanilce Pereira de (2017)
The technological development has allowed advances and setbacks to modern society when it comes to wildlife. Faced with this situation, the zoos are becoming more recognized and respected spaces, since they provide the survival of rare or endangered species that are no longer found and developed in natural areas, or that are victims of hunting, running overs or animal trafficking (ARAGÃO, 2014). In this context, it is stated that the presence of Environmental Education at the zoos presents great potential for spreading information about the regional and global fauna, besides contributing to the formation of habits and positive attitudes regarding the environment preservation (GARCIA, 2006). In other words, it promotes awareness for the visiting public as much as it brings out the preoccupation towards the consequences of the destruction of biological diversity, by stimulating positive attitudes (MARINO, 2008). Therefore, this dissertation aims to evaluate the environment perception of the visiting public of the Municipal Zoo of Cascavel, using the semiotic developed by Charles Sanders Peirce, and to validate the construction of two pedagogic intruments (Intrument I – for children between 06 and 11 years old; Instrument II – for adolescents and young between 12 to 21 years old). The pedagogic instruments were answered by 924 students, between october 2015 and january 2016. The obtained results were gruped in three analytical categories: 1) knowledge level, 2) comprehension level and 3) human and non-human interaction level. Upon this verification, it can be concluded that the instruments are efficient for the evaluation of the environmental perceptions of the visiting public of the Municipal Zoo of Cascavel – PR, for presenting ludic, informative and scientific characteristics; furthermore it contributes to the insertion of new knowledge and the upbringing of new perceptions surrounding the preservation of animals and the environment they live on.